Shedding light on the fungal darkness: cave fungi from the Southern Espinhaço mountain range of Minas Gerais - Condé, Thiago Oliveira (2023)
Interest in cave fungal diversity is flourishing because it may represent a reservoir of new species and metabolites. However, the mycobiota remains poorly studied in the underground environment, especially in Neotropical regions. During surveys that aimed to investigate the fungal diversity in quartzite and karst caves in the Southern Espinhaço Mountain in Brazil, six Chaetomiaceae isolates were obtained from different cave substrates. Five taxonomical novelties of Chaetomiaceae in Brazilian caves were discovered based on phylogenetic analyses using DNA sequences from ITS, LSU, TUB, and RPB2 genes. Chaetomium meridionalense, Pseudohumicola alba and Pseudohumicola lutea are new species found in Gruta da Extração and Gruta Velha Nova caves. Parahumicola is introduced as a new genus representing a novel phylogenetic lineage with unique morphological characteristics in the family Chaetomiaceae. This new monotypic genus is typified by P. guana, which was found in a bat guano sample in the Gruta Monte Cristo cave. Furthermore, this is the first report of Collariella bostrychodes in a neotropical cave. Overall, these findings emphasize that Brazilian caves constitute an untapped source of fungal resources. Keywords: Five new taxa. Biospeleology. Chaetomium. Parahumicola. Pseudohumicola. Sordariales.